PERAN MSF (MÉDECINS SANS FRONTIÈRES) DALAM MENANGANI EPIDEMI EBOLA DI AFRIKA BARAT TAHUN 2012-2014 - Yorry Hasanah; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
research describes how Médecins Sans Frontières (MSF) handling Ebola epidemic in Western Africa. MSF is an international, independent, medical humanitarian organization. The Ebola virus causes an acute, serious illness which is often fatal if untreate. The current outbreak in West Africa that is the largest and most complex Ebola outbreak since the Ebola virus was first discovered in 1976. Since 2012 up to 2014 have been many reported cases of ebola. This study is a qualitative research method that used the concept of human security and international organization theory. The writer concluded that MSF has intense role in handling epidemic Ebola in Western Africa. This is indicated by all the activities that have been carried out since the Ebola outbreak and many cases reported. The programs are conducted by MSF in the form of providing financial assistance, logistical support, as well as handling activities by establishing many CMCs (case management centre.Keywords : Ebola, Epidemic, Médecins Sans Frontières (MSF), Western Africa.